Sabbatical leave report: Spring 2014 - Heidkamp, C. Patrick (2014)
The proposed research project focused on analyzing food system resilience in a small town in eastern Iceland from the perspective of environmental economic geography. In addition to the stated project Heidkamp initiated "a new research project focused on the uniqueness of Nordic Environments, Nordic Spaces and Nordic Places." The sabbatical study yielded panelist and lecturer invitations and conference papers and presentations.
Keywords: dept.egm; faculty_collection; sabbatical_report

American Geography and Geographers: Toward Geographical Science - Martin, Geoffrey J. (Oxford University Press, 2014)
The rise of American geography as a distinctive science in the United States straddles the 19th and 20th centuries, extending from the post-Civil war period to 1970. American Geography and Geographers: Toward Geographic Science is the first book to thoroughly and richly explicate this history. Its author, Geoffrey J. Martin, the foremost historian on the subject and official archivist of the Association of American Geographers, amassed a wealth of primary sources from archives worldwide, which enable him to chart the evolution of American geography with unprecedented detail and context. From the initial influence of the German school to the emergence of Geography as a unique discipline in American universities and thereafter, Martin clarifies the what, how and when of each advancement. Expansive discussion of the arguments made, controversies ignited and research voyages move hand in hand with the principals who originated and animated them: Davis, Jefferson, Huntington, Bowman, Johnson,, Sauer, Hartshorne, and many more. From their grasp of local, regional, global and cultural phenomena, geographers also played pivotal roles in world historical events, including the two world wars and their treaties, as the US became the dominant global power. American Geography and Geographers: Toward Geographical Science is a conclusive study of the birth and maturation of the science. It will be of interest to geographers, teachers and students of geography, and all those compelled by the story of American Geography and those who founded and developed it.
Keywords: Geography; History; History; Geographers; History; United States; Study and teaching; Study and teaching (Higher); United States; dept.egm; faculty_collection

Two new Peruvian species of Jaltomata (Solanaceae, Solaneae) with red floral nectar - Mione, Thomas; González, Segundo Leiva; Yacher, Leon (Brittonia, 2014)
Two new Jaltomata species (Solanaceae) of Peru that produce red floral nectar are described. Jaltomata neei of Department Cajamarca has 1–4 flowers per inflorescence, the campanulate corolla is green and then changes to blue, corolla lobes (5) and lobules (5) are equally prominent, a corona is lacking, five radial staminal-corolla thickenings create nectar troughs between, and the stigma is capitate. Jaltomata quipuscoae of Department Arequipa has solitary flowers, a purple, broadly crateriform, 5-lobed corolla, a corona on which nectar pools, a punctiform stigma, lacks corolla thickenings, and the mature fruit is whitish. Photographs, illustrations and tables are included that allow comparison with closely related species. © 2014, The New York Botanical Garden.
Keywords: Arequipa; Cajamarca; Jaltomata neei; Jaltomata quipuscoae; Peru; corolla color change; corona; dept.egm; lomas; protogyny; red nectar

Metals, Organic Compounds, and Nutrients in Long Island Sound: Sources, Magnitudes, Trends, and Impacts - Varekamp, Johan C.; McElroy, Anne E.; Mullaney, John R.; Breslin, Vincent T. (Long Island Sound: Prospects for the Urban Sea, 2014)
Long Island Sound (LIS) is a relatively shallow estuary with a mean depth of 20 m (maximum depth 49 m) and a unique hydrology and history of pollutant loading. These factors have contributed to a wide variety of contamination problems in its muddy sediments, aquatic life, and water column. The LIS sediments are contaminated with toxic compounds and elements related to past and present wastewater discharges and runoff. These include nonpoint and stormwater runoff and groundwater discharges, whose character has changed over the years along with the evolution of its watershed and industrial history. Major impacts have resulted from the copious amounts of nutrients discharged into LIS through atmospheric deposition, domestic and industrial waste water flows, fertilizer releases, and urban runoff. All these sources and their effects are in essence the result of human presence and activities in the watershed, and the severity of pollutant loading and their impacts generally scales with total population in the watersheds surrounding LIS. Environmental legislation passed since the mid-to-late 1900s (e.g., Clean Air Act, Clean Water Act) has had a beneficial effect, however, and contaminant loadings for many toxic organic and inorganic chemicals and nutrients have diminished over the last few decades (O’Shea and Brosnan 2000; Trench et al. 2012; O’Connor and Lauenstein 2006; USEPA 2007). Major strides have been made in reducing the inflow of nutrients into LIS, but cultural eutrophication is still an ongoing problem and nutrient control efforts will need to continue. Nonetheless, LIS is still a heavily human impacted estuary (an “Urban Estuary,” as described for San Francisco Bay by Conomos 1979), and severe changes in water quality and sediment toxicity as well as ecosystem shifts have occurred since the European colonization in the early 1600s (Koppelman et al., 1976). The Sound has seen the most severe environmental changes over the last 400 years during its 10,000 year history (Lewis, this volume), suggesting that human impacts have overwhelmed the natural forces at play.
Keywords: Boston Harbor; Coastal Embayment; Marine Organic Matter; Striped Bass; White Perch; dept.egm